2021
DOI: 10.1002/batt.202000317
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine Complexes as Tailored Precursors for Rapid Synthesis of Thiophosphate Superionic Conductors

Abstract: Room temperature solution synthesis of electrolytes for all‐solid‐state batteries has garnered much interest in the past years as a more scalable and efficient alternative to traditional solid‐state syntheses. Li3PS4, a model solid electrolyte often studied, is typically produced from Li2S and P4S10; the latter exists as a molecular solid in an adamantane‐like cage structure, and it has been posited that from its robustness arises a rate‐limiting reaction step. In this work, we have applied chemistry inspired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…It was recently reported that strong interactions of pyridine (py) and thiophosphate groups lead to the breakage of P 4 S 10 adamantane cages into the stabilized py 2 P 2 S 5 complex. 65 Interestingly, the conductivity after treatment with pyridine is still relatively high (6•10 −4 S cm −1 ), indicating that strong solvent−thiophosphate interactions are not necessarily detrimental for the performance. Taken together, the results indicate that the residual solvent acts as a low conductivity phase that significantly hinders, and possibly dominates, the measured ionic conductivity of the processed samples.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently reported that strong interactions of pyridine (py) and thiophosphate groups lead to the breakage of P 4 S 10 adamantane cages into the stabilized py 2 P 2 S 5 complex. 65 Interestingly, the conductivity after treatment with pyridine is still relatively high (6•10 −4 S cm −1 ), indicating that strong solvent−thiophosphate interactions are not necessarily detrimental for the performance. Taken together, the results indicate that the residual solvent acts as a low conductivity phase that significantly hinders, and possibly dominates, the measured ionic conductivity of the processed samples.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The latter is most evident for the pyridine-treated LiSiPS in which, despite a vapor pressure similar to toluene (20 hPa at 20 °C), a large fraction of it remains in the sample. It was recently reported that strong interactions of pyridine (py) and thiophosphate groups lead to the breakage of P 4 S 10 adamantane cages into the stabilized py 2 P 2 S 5 complex . Interestingly, the conductivity after treatment with pyridine is still relatively high (6·10 –4 S cm –1 ), indicating that strong solvent–thiophosphate interactions are not necessarily detrimental for the performance.…”
Section: Resultsmentioning
confidence: 99%
“…Solution synthesis is an efficient and cost-effective approach to prepare sulfide based solid electrolytes, with a large number of organic solvents, such as ethanol, acetonitrile (ACN), N -methylformamide (NMF), and tetrahydrofuran (THF). ,, Recently, researchers have prepared Li 3 PS 4 solid electrolyte using pyridine solvent and have obtained well-crystallized material with reasonable ionic conductivity . Pyridine is a well-known thionation agent and easily dissolves P 2 S 5 to form the P 2 S 5 ·pyridine complex.…”
Section: Introductionmentioning
confidence: 99%
“…1,8,9 Recently, researchers have prepared Li 3 PS 4 solid electrolyte using pyridine solvent and have obtained well-crystallized material with reasonable ionic conductivity. 10 Pyridine is a well-known thionation agent and easily dissolves P 2 S 5 to form the P 2 S 5 •pyridine complex. Li 2 S can easily react with the P 2 S 5 • pyridine complex to form Li 2 S−P 2 S 5 -type solid electrolytes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The synthesis of Li 3 PS 4 using liquid-phase synthesis with organic solvents as reaction media has been intensively investigated recently as an alternate chemical route for the preparation of sulfide-based solid electrolytes rather than the conventional solid state reaction [11][12][13][14][15][16]. In most of the reports, the effect of the solvents on the formation of Li 3 PS 4 was of primary interest [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%